ANALISIS RESEPSI KHALAYAK TERHADAP DISCREET HOMOSEXUAL PADA FILM DEAR DAVID - Nurhadelia Wihenny (2023)
The purpose of this research is to understand how the audience receives and forms meanings about discreet homosexuality in the film "Dear David" influenced by their backgrounds and experiences. This research began from the phenomenon of the public's numerous criticisms regarding the portrayal of discreet homosexual issues in the character Dilla in the film "Dear David. .The research method used is descriptive qualitative using Stuart Hall's reception analysis. Reception analysis is used to determine the audience's positions based on Stuart Hall's three categories: Dominant Hegemonic Position, Negotiated Position, and Oppositional Position. The results of this research show that three informants are in the dominant position, two informants are in the negotiated position, and one informant is in the oppositional position. The meanings constructed by the informants regarding the portrayal of discreet homosexuality in the film "Dear David" are divided into three categories: mindset, feelings, and behavior, and the informants produce different feelings and responses towards discreet homosexuality in the film as well as in everyday life. The audience perceives the message in the film in various ways which causes controversy. This controversy is related to the stigmatization of homosexual which leads to discrimination The diverse interpretations of the informants are influenced by differences in backgrounds such as age, culture, religion, occupation, domicile, thoughts, and life experiences of each informant.